Automation and market opportunity analysis through the TAM SAM SOM methodology for new business development (2024)
Globalization has allowed companies to develop processes in order to be competitive and position themselves in the market. The high demand and supply of products and/or services have created the need to seek methods where skills such as adaptation and optimization play an important role in generating value for the company. Likewise, the creation of strategies to optimize resources will be reflected in cost reduction and in the efficiency with which projects evolve, as well as in the way they respond to market needs. Nowadays, thanks to important technological advances, value has been generated in the development of business processes, allowing the automation of processes for the extraction of data that produce valuable information for companies, allowing them to identify opportunities to enter international markets, as well as decision making, the efficient adaptation of strategies and the development of innovative business models to meet market demand. The TAM SAM SOM is a model that has generated a great impact on business models as it allows companies to define the size and scope of the target market they wish to reach with their products and/or services, which is why elements as important as the data collected and a good analysis generate market visibility, where from that, measures are taken for the implementation of projects and strategies are proposed, capabilities and entry methods are identified, and decisions are made that generate business opportunities which are exploited by companies that are increasingly in a competitive international market. This project seeks to propose an improvement plan through the automation of the TAM SAM SOM with the purpose of developing projects focused on the health sector in the Biosciences area in a short time through data extracted from official sources, in this case CEPAL is used as a source, where through its API obtained from its CEPALSTAT database, the collected data is extracted and will be evidenced in a dynamic Power BI dashboard through interactive graphs that allow a better analysis of the information.